Optimasi Parameter Vacuum Assisted Resin Infusion (VARI) Produk Bilah Turbin Angin Terhadap Uji Bending - Hidayat, Alfin Nur Hidayat Nur (Motor Bakar : Jurnal Teknik Mesin, 2025)
This research aims to optimize the parameters of the Vacuum Assisted Resin Infusion (VARI) method in the production of composite specimens and wind turbine blade products to enhance mechanical strength, particularly bending strength. The research was conducted with variations in parameters including fiber volume (10% and 20%), vacuum pressure (0.6 bar and 0.8 bar), and catalyst (1% and 2%). The variations were tested using bending tests and loading tests, and then the Taguchi method was used to identify the parameter combinations that produced the best performance. The bending test results show that a 20% fiber volume variation yields the highest average bending test result of 198.20 MPa, compared to a 10% fiber volume which only reaches 112.20 MPa. A vacuum pressure of 0.6 bar yields a bending test result of 198.20 MPa, which is better compared to a vacuum pressure of 0.8 bar with an average bending test result of 112.20 MPa. The 1% catalyst variation produced the highest bending test value of 198.20 Mpa, higher than the 2% catalyst variation, which yielded a bending test value of 125.13 Mpa. The conclusion of this study is that the optimal combination for producing the best bending test is using a fiber volume of 20%, a vacuum pressure of 0.6 bar, and a catalyst of 1%. This research provides important insights into the development of lighter, stronger, and more environmentally friendly composite materials, which can be used as an alternative to metals in various industrial applications, including the manufacturing of wind turbine blade products.